Comfort Measures Only : New and Selected Poems, 1994-2016 - Campo, Rafael (Book collections on Project MUSE., 2018)
Gathered from Rafael Campo's over twenty year career as a poet-physician, these eighty-eight poems--thirty of which have never been previously published in a collection--pull back the curtain in the ER, laying bare our pain and joining us all in spellbinding moments of pathos.